Optical transparency of mesoporous metals - N. Stefanou; A. Modinos; V. Yannopapas (Solid State Communications, 2001)
We examine the optical properties of metals containing a periodic arrangement of nonoverlapping spherical mesopores, empty or filled with a dielectric material. We show that a slab of such a porous metal transmits light over regions of frequency determined by the dielectric constant of the cavities and the fractional volume occupied by them, with an efficiency, which is many orders of magnitude higher than predicted by standard aperture theory. Also, the system absorbs light efficiently over the said regions of frequency unlike the homogeneous metal.